1995
DOI: 10.2172/116621
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocyanide safety project ferrocyanide aging studies FY 1995 annual report

Abstract: SummaryThis annual report gives the results of the work conducted by the Pacific Northwest Laboratory in FY 1995 on Task 3 of the Ferrocyanide Safety Project, Ferrocyanide Aging Studies. Aging refers to the dissolution and hydrolysis of simulated Hanford ferrocyanide waste in alkaline aqueous solutions by radiolytic and chemical means. The ferrocyanide simulant primarily used in these studies was driedIn-Farm-lB, Rev. 7, prepared by Westinghouse Hanford Company to simulate the waste generated when the In-Farm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Interestingly, wastes in Tanks BY-lOS, C-I0S, C-109, and C-112 were scavenged with ferrocyanide to precipitate the J37Cs as NaCsNiFe(CN)6 or Cs 2 NiFe(CNk The Cs being present would explain the 137CS behavior during washing and caustic leaching as the nickel ferrocyanide salts in these wastes. Recent studies have shown that Na2NiFe(CN)6 decomposes by both radio lytic and hydrolytic mechanisms under conditions that would be expected in the Hanford tanks, and it has been suggested that these pathways would have led to a reduction in the overall ferrocyanide concentrations in the sludges (Lilga et al 1995). However the cesium nickel ferrocyanide salts are less soluble in aqueous NaOH (Bryan et al 1993;Lilga et al 1995), so their decomposition might be slower than the Na analog.…”
Section: Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, wastes in Tanks BY-lOS, C-I0S, C-109, and C-112 were scavenged with ferrocyanide to precipitate the J37Cs as NaCsNiFe(CN)6 or Cs 2 NiFe(CNk The Cs being present would explain the 137CS behavior during washing and caustic leaching as the nickel ferrocyanide salts in these wastes. Recent studies have shown that Na2NiFe(CN)6 decomposes by both radio lytic and hydrolytic mechanisms under conditions that would be expected in the Hanford tanks, and it has been suggested that these pathways would have led to a reduction in the overall ferrocyanide concentrations in the sludges (Lilga et al 1995). However the cesium nickel ferrocyanide salts are less soluble in aqueous NaOH (Bryan et al 1993;Lilga et al 1995), so their decomposition might be slower than the Na analog.…”
Section: Radionuclidesmentioning
confidence: 99%
“…Recent studies have shown that Na2NiFe(CN)6 decomposes by both radio lytic and hydrolytic mechanisms under conditions that would be expected in the Hanford tanks, and it has been suggested that these pathways would have led to a reduction in the overall ferrocyanide concentrations in the sludges (Lilga et al 1995). However the cesium nickel ferrocyanide salts are less soluble in aqueous NaOH (Bryan et al 1993;Lilga et al 1995), so their decomposition might be slower than the Na analog. Indeed, ferrocyanide has been detected in actual C-109 and C-l12 sludges at levels close to 1 molo (Bryan et al 1995).…”
Section: Radionuclidesmentioning
confidence: 99%
“…Hydrogen cyanide is an unlikely product of the degradation of complex metal ferrocyanides under tank conditions. High ammonia concentrations are also associated with the aging of ferrocyanide wastes (Lilga 1992(Lilga , 1993(Lilga , 1994(Lilga , 1995. As expected, none of the Ferrocyanide Watch List tanks sampled for hydrogen cyanide contained any credible indications of its presence.…”
Section: Ferrocyanide Degradation Productsmentioning
confidence: 67%
“…Recent aging studies of ferrocyanide waste show that the combined effects of temperature, radiation, and pH during 38 years or more of storage would have destroyed most of the ferrocyanide originally added to the tanks (Babad et al 1993;Lilga et al 1993Lilga et al , 1994Lilga et al , 1995Lilga et al and 1996. This prediction has been confirmed by the tank samples analyzed to date.…”
Section: Ferrocyanide Degradationmentioning
confidence: 84%